2012
DOI: 10.1111/j.1464-5491.2012.03567.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring of blood glucose in Type 2 diabetes: cross-sectional analyses in 1993, 1999 and 2009

Abstract: strips, and among non-insulin-treated patients this was commoner among women, younger people and less deprived groups. Conclusions: The numbers of reagent strips dispensed for SMBG has increased, and almost all insulin-treated patients receive strips. While few diet-treated patients receive strips, they are more extensively dispensed to those treated with oral agents. Given that SMBG is no longer routinely recommended in non-insulin treated patients, strategies to reduce unnecessary dispensing of reagent strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The screening and selection process are shown in Figure 1, while Table 1 present the main characteristics of the studies included. n=1 062 Embase (523) Science Direct (23) PubMed (468) Scielo (2) Cochrane (1) Medline (45) Vaca-González et al (8) Excluded records 1 036…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The screening and selection process are shown in Figure 1, while Table 1 present the main characteristics of the studies included. n=1 062 Embase (523) Science Direct (23) PubMed (468) Scielo (2) Cochrane (1) Medline (45) Vaca-González et al (8) Excluded records 1 036…”
Section: Resultsmentioning
confidence: 99%
“…(40)(41)(42)(43) Self-monitoring of blood glucose in in insulin-treated type 2 diabetes mellitus Currently, SMBG is considered an essential component in the management of insulin-treated T2DM patients and its use is mandatory. (17,18) In this regard, Schnell et al (45) found that use of SMBG in these patients increased by 23% between 1993 and 2009. Also, there are many prospective and observational studies addressing the use of SMBG in insulin-treated T2DM patients.…”
Section: Self-monitoring Of Blood Glucose and Patient Educationmentioning
confidence: 98%
“…The effect of deprivation on frequency of testing has been noted by several authors, in particular in type 2 diabetes, and is a concern given its potential to widen inequalities in diabetes outcomes . It is important that everyone who is treated with insulin and for whom SMBG may be beneficial has appropriate knowledge about testing recommendations and the practice of self‐monitoring .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a general increase in SMBG over the past two decades in the UK and elsewhere . Frequency of testing has increased, alongside increases in the numbers of those testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation